MARKETING MIX IN SPORT - Srećko Novaković; Slobodan Živkucin (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
Marketing mix'' along the term of life cycle has robbed the trademark for the conception of marketing and the market direction of company, corporations and institutions. Essence marketing-mixa is in the simultaneous determining of the target market group of consumer (the buyer) or stays the public and specially prepared and the coordinated impact of elements mixa, and this is the product, price, distributions and graduation ceremonies. Given that is mix combinations of verified variables, companies he use in order to would achieve are wished the scope sales on the target market. In the wider context significant influence of environment on the chosen structure marketing-mixa have not only technological, economic and competitive services already and socially-owned, legislative, legal and political services. From those reasons chant the marketing -mixa occasionally replaces expression are coordinated term acts on the market. Elements marketing-mix-and at sport marketings same are as well as at marketings every other activity. They contain the sportively product and the service, appreciate the sport product and services, distribution of sport product and services and the promotion of sport product and services.